ANALISIS IMPLIKATUR DALAM SERIAL ANIMASI ADIT SOPO JARWO - Auliawati, Sri; Syahrani, Agus; Muzammil, Ahmad Rabiâ€™ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract.This thesis is entitled "Implicature Analysis in Adit Sopo Jarwo animated series." This research is motivated so that the reader understands the additional meaning or implied meaning of a speech that is not directly expressed through the vocabulary used, so that the expressions expressed by the speaker are well conveyed to the speech partner. This study aims to describe conventional implicature, types of non-conventional implicature, and learning implementation plan. The method in this research is descriptive method. The form of research used is qualitative research. The source of data in this study is the video documentary series Adit Sopo Jarwo animation. The data in this study are words, phrases and sentences which are conventional and non-conventional implicatures in the Adit Sopo Jarwo animated series. Data collection techniques in this research are documentary studies. Data collection tool in this study is the author as a key instrument. The data analysis technique used in this research is descriptive qualitative. Based on data analysis, the results obtained are 7 conventional implicature data, 61 non-conventional implantature data which are divided into 37 general conversation implicature data, 11 scale implicator data, and 13 special conversation implicature data, and learning implementation plans in the form of Learning Implementation Plan (RPP) on even VIII semester grade review text material.Â Keywords: Implicature Analysis, Film Series, Animation Adit Sopo Jarwo